Biocompatible osimertinib nanoliposomes coated with PEGylated hyaluronic acid enhanced tumor selectivity and cytotoxicity via CD44-mediated NSCLC targeting: Development, characterization and in-vitro biochemical studies - Sanjay Kumar Kuna, Asha Deepti Choppala (Journal of Applied Pharmaceutical Science, 2023)
Osimertinib (OMB) is an irreversible TK inhibitor approved to treat cancers with epidermal growth factor receptor (EGFR) mutations. Despite its high solubility and absorption, its poor tumor selectivity and off-target systemic toxicity pose problems to its effectiveness and safety. This study aimed to enhance tumor-targeted delivery of OMB via CD44 targeting by developing an effective OMB-nanoliposomal formulation for overcoming challenges associated with conventional OMB delivery. OMB-loaded liposomal formulations were developed using a freeze-drying method, and all were successfully characterized, including in-vitro OMB release. non-small cell lung cancer models H1975 and PC-9 cells were used to study hyaluronan-CD44 receptor targeting, cellular uptake, and cytotoxicity. All formulations exhibited superior characteristics of size, zeta potential, and PDI with high encapsulation efficiency. Among all formulations, mPEG-hyaluronic acid (HA) (mds)-OMB-LPs demonstrated long-term in-vitro drug release, with a cumulative % drug release of 99.99% ± 2.58% up to 72 hours stating the sustained release of OMB at pH 7.4. The cellular uptake and cytotoxicity of mPEG-HA coated LPs at a 1:1 was greater than those of OMB-LPs, as well as Tagrisso in both the cells overexpressing CD44, whereas the effect was lower in PC-9 cells having low CD44 expression. It is evident from these findings that successful liposomal formulations are taken up by cells via CD44-mediated processes. As compared with plain OMB solution, mPEG-HA-OMB-LPs increased in-vitro accumulation and cytotoxicity in both H1975 and PC-9 cells with activating EGFR mutations.